Modified MXene-based silicon-carbon composite material and preparation method thereof, negative electrode and battery

MXene was prepared by etching the MAX phase and electrostatically adsorbing graphene quantum dots to form a modified MXene protective layer, which solved the problem of insufficient conductivity of silicon-carbon composite materials, achieved high conductivity and high temperature resistance, and improved the magnification of lithium-ion batteries Performance and stability.

CN119208556APending Publication Date: 2024-12-27AMPREUS WUXI CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411304172.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The weak conductivity of silicon-carbon composite materials in lithium-ion batteries leads to poor rate performance, and the reaction between silicon and carbon during high-temperature graphitization has been carried out to generate silicon carbide, reducing conductivity and increasing costs.

Method used

MXene is prepared by etching the MAX phase by etching agent, electrostatically adsorbing graphene quantum dots to form modified MXene material, and uses it to the porous carbon material coated with silicon nanoparticles in the liquid phase to form a highly conductive, high temperature and oxidation-resistant protective layer, which enhances the The conductivity of silicon-carbon composite materials.

Benefits of technology

The conductivity and oxidation resistance of silicon-carbon composite materials are significantly improved, allowing full graphitization at high temperatures, and the battery maintains 88% discharge energy under 10C discharge, overcoming the problems of conductivity and expansion rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208556A_ABST
    Figure CN119208556A_ABST
Patent Text Reader

Abstract

The invention relates to a silicon-carbon composite material based on modified MXene, a preparation method of the silicon-carbon composite material, a negative electrode and a battery. MXene is prepared by etching an MAX phase through an etching agent; the preparation method comprises the following steps: preparing graphene quantum dots B-GQD and P-GQD + respectively; the graphene quantum dots B-GQD, the graphene quantum dots P-GQD + and the MXene are self-assembled through electrostatic adsorption, and a modified MXene material B / P-GQD / MXene is formed; preparing a porous carbon material deposited with silicon nanoparticles; the modified MXene material B / P-GQD / MXene is adopted to carry out liquid phase coating on the porous carbon material deposited with the silicon nanoparticles, and the silicon-carbon composite material based on the modified MXene is formed. The conductivity of the silicon-carbon composite material can be enhanced, and the rate capability of the lithium ion battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and particularly relates to a silicon-carbon composite material based on modified MXene, a preparation method thereof, a negative electrode, and a battery. Background Art

[0002] Developing high-energy-density lithium-ion batteries is the only way to meet the key requirements of longer battery life and lighter weight for electronic products (such as laptops, mobile phones, power tools, etc.) and electric vehicles. However, the specific capacity of graphite, which is currently widely used as the main negative electrode material for lithium batteries, has tended to reach the limit of 372 mAh·g -1 , and it is very difficult to make a lithium battery with a higher energy density using a pure graphite material negative electrode solution.

[0003] Among all potential lithium-ion battery negative electrode materials, silicon (Si) is considered to be one of the most promising candidate materials for next-generation high-energy lithium-ion batteries. Si has the following attractive properties: (1) Based on the all-lithiation alloying process of Li 22 Si4, silicon can theoretically provide a high capacity of up to 4200 mAhg -1 , which is more than ten times higher than that of graphite; (2) Si has a suitable lithiation voltage platform of ≈0.3 V (vs Li / Li+); (3) Si is the second most abundant element in the earth's crust, with environmental friendliness and non-toxicity, which is conducive to low-cost and large-scale production. However, when the Si material forms Li 22 Si4 during lithiation, the volume expands by up to 360%, which will cause serious electrode pulverization. The fragmentation of the Si material will also cause the solid electrolyte interface (SEI) to split and fall into a cycle of SEI film reconstruction and regeneration, consuming a large amount of active lithium. On the other hand, the electronic conductivity of silicon is very poor (≈10 -3 Scm -1 ), which will inevitably greatly weaken the kinetics of the negative electrode. Therefore, directly using pure silicon as the negative electrode material of the battery will bring various potential hazards. Compared with silicon, silicon suboxide (SiO x , 0 < x ≤ 2) has a relatively low volume expansion rate (≈200%) and a relatively high theoretical lithium storage capacity (2200 - 3850 mAhg -1), however, the initial efficiency of silicon oxide material is very low. Pre-lithiation of silicon oxide can reduce the consumption of lithium ions when the battery is first charged, thereby improving the initial efficiency, but it will greatly increase the material cost and the process is also more complicated. In order to solve the problems of silicon and silicon-oxygen materials, the vapor deposition method (CVD) to prepare silicon-carbon composite materials came into being. The core of this preparation method is to store silicon through a porous carbon skeleton. First, a carbon skeleton with a porous structure similar to a sponge is made with polymer materials, and then silane gas is introduced into the pores of the porous carbon skeleton. The gas is precipitated into silicon nanoparticles dispersed in the pores of the porous carbon through high-temperature pyrolysis. This method can achieve molecular-scale control of the prepared nanomaterials, and the product morphology is good. At the same time, the silicon-carbon material produced by deposition has uniform components and a relatively dense structure. The volume expansion is buffered by the voids inside the porous carbon, so the expansion rate is low and the cycle is excellent. The problem with silicon-carbon composites is that they have weak electrical conductivity, which leads to rate problems. Coating a layer of carbon and increasing the temperature to graphitize the carbon layer is currently a common solution to enhance the electrical conductivity of silicon-carbon composites. However, the graphitization of good carbon materials requires temperatures as high as thousands of degrees Celsius, which will inevitably cause silicon and carbon to react to form silicon carbide (SiC). If SiC is not treated in any way, the energy barrier for lithium ions to insert into SiC is very high, making it impossible to embed lithium. Moreover, the generation of SiC as a semiconductor material will greatly reduce the electrical conductivity of silicon-carbon composites. Therefore, the key to improving the electrical conductivity of silicon-carbon composites is how to treat the deposited silicon nanoparticles.

[0004] MXene is a general term for transition metal nitrides, carbides, and nitrogen carbides, with the general formula being M n+1 X n T X (n=1-4), where M represents a transition metal, X represents carbon and nitrogen, T X It is the surface termination group of MXene (-OH, -F, -O, -Cl, etc.). There are many methods for MXene materials. The core is to remove the group A elements in the precursor MAX phase, and MXene can be customized through specific synthesis methods to amplify specific functions.

[0005] Graphene quantum dots (GQDs) are a 0D graphene-based material consisting of one or several layers of graphene, with a lateral size usually less than 30nm, and a structure in which each carbon forms a triangular plane orbital geometry and is tightly bound to three adjacent carbon atoms. GQDs have quantum size effects and edge effects, which give GQDs unique optical properties, conductivity, heat resistance and stability. Various amino acids added during the synthesis process can obtain GQDs with different functionalizations, and GQDs with different functional groups can be customized as needed. Summary of the invention

[0006] The purpose of the present invention is to provide a silicon-carbon composite material based on modified MXene and its preparation method, negative electrode and battery to address the problem that the current silicon-carbon composite material has weak conductivity, resulting in poor rate performance of lithium-ion batteries containing the material.

[0007] To achieve the above purpose, the technical solution provided by the present invention is:

[0008] The first aspect of the present application provides a method for preparing a silicon-carbon composite material based on modified MXene, characterized in that it comprises the following steps:

[0009] Prepare MXene by etching the MAX phase with an etchant;

[0010] Prepare graphene quantum dots B-GQD and P-GQD respectively + ;

[0011] The graphene quantum dots B-GQD and P-GQD + Self-assembly with the MXene through electrostatic adsorption to form a modified MXene material B / P-GQD / MXene;

[0012] Preparation of porous carbon materials depositing silicon nanoparticles;

[0013] The modified MXene material B / P-GQD / MXene is used to perform liquid phase coating on a porous carbon material with deposited silicon nanoparticles to form a silicon-carbon composite material based on the modified MXene.

[0014] In order to optimize the above technical solutions, the following limitations are also adopted:

[0015] The etchant is lithium fluoride and hydrochloric acid; the MAX is Ti3C2T X .

[0016] Addition of B-GQDs and P-GQDs to MXene + The addition amounts were 15wt% and 10wt%, respectively.

[0017] Preferably, the etching time is 12h-48h, and the etching temperature is 25°C-40°C; after etching, the pH of the solution is adjusted to neutral to collect MXene, and ascorbic acid is added to the MXene obtained by etching.

[0018] The graphene quantum dots B-GQD are prepared by hydrothermal method using citric acid and boric acid, and the graphene quantum dots P-GQD + It is prepared from citric acid and phytic acid by a hydrothermal method.

[0019] Furthermore, the method for preparing the porous carbon material with deposited silicon nanoparticles is as follows:

[0020] The acid-based resin and the organic base pore-forming agent are mixed and reacted in a mass ratio of 100:1-10, and after drying, carbonized at a temperature of 700-900°C for 1-6h;

[0021] Silane gas is introduced into the pores of the porous carbon substrate by vapor deposition, and the gas is precipitated into silicon nanoparticles dispersed in the porous carbon pores through high-temperature pyrolysis, so that the deposited silicon nanoparticles occupy 45%-55% of the porous carbon void volume.

[0022] The liquid phase coating time is 60 minutes to 100 minutes, and the modified MXene-based silicon-carbon composite material is obtained by drying after the liquid phase coating.

[0023] The second aspect of the present application provides a silicon-carbon composite material based on modified MXene prepared by the method, wherein the surface of the silicon-carbon composite material has a modified MXene protective layer, and the modified MXene protective layer contains a P / N heterogeneous structure.

[0024] The third aspect of the present application provides a negative electrode sheet, which comprises the silicon-carbon composite material provided in the second aspect of the present application.

[0025] The fourth aspect of the present application provides a battery, which comprises the negative electrode sheet provided in the third aspect of the present application.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The present invention uses an improved etchant formula and a synthesis method to etch the MAX phase to prepare MXene; and prepares positively charged and negatively charged graphene quantum dots P-GQD respectively by a hydrothermal method. + , B-GQD; graphene quantum dots and MXene are self-assembled into highly conductive, high temperature and oxidation resistant modified MXene materials through electrostatic adsorption; in the preparation of silicon-carbon composite materials, the porous carbon material deposited with silicon nanoparticles is liquid-phase coated with the highly conductive, high temperature and oxidation resistant modified MXene material to give the silicon nanoparticles a MXene protective layer, thereby enhancing the conductivity of the silicon-carbon composite material.

[0028] The modified MXene material of the present invention has the following advantages when used in silicon-carbon composite materials:

[0029] (1) The improved etchant formula and synthesis method have a strong control effect on the surface groups of MXene, reducing the water content of the material, protecting Ti that is easily oxidized, and giving MXene materials high temperature and oxidation resistance without affecting conductivity;

[0030] (2) B-GQD and P-GQD +Through electrostatic interaction, B-GQDs can self-assemble with MXene. B-GQDs carry negative charges and can be assembled on the end faces of MXene to protect the end groups that are easily oxidized. In addition, B-GQDs can self-assemble with MXene as a P-type semiconductor. + (N-type semiconductor) With MXene as the substrate, the three are closely adsorbed to form a P / N heterojunction; the introduction of negatively charged B-GQD protects the end group of MXene and improves the antioxidant stability. + The introduction of MXene and B-GQD forms a P / N heterostructure, which improves the conductivity of B / P-GQD / MXene materials.

[0031] (3) The introduction of two quantum dots can significantly improve the problem of sudden decrease in conductivity caused by the stacking of MXene sheets due to the strong van der Waals force between the sheets;

[0032] (4) The silicon nanoparticles protected by the highly conductive, high temperature and oxidation resistant modified MXene material protective layer can reach a graphitization temperature of over 1000°C during the final carbon coating step; thanks to the highly conductive MXene protective layer and the full graphitization due to its high temperature and oxidation resistance, the silicon-carbon composite material has good conductivity (including the battery made of it has a discharge energy retention rate of 88% under 10C discharge). BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is the room temperature cycle diagram of a battery made of a silicon-carbon composite material with a modified MXene protective layer.

[0034] Figure 2 This is the room temperature cyclic expansion diagram of a battery made of a silicon-carbon composite material with a modified MXene protective layer. DETAILED DESCRIPTION

[0035] The above contents of the present invention are further described in detail below in the form of embodiments, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies realized based on the above contents of the present invention belong to the scope of the present invention.

[0036] The test methods used in the following examples are all conventional methods unless otherwise specified, and the reagents, methods and equipment used are all conventional reagents, methods and equipment in the art unless otherwise specified.

[0037] For the sake of simplicity, this document only specifically discloses some numerical values ​​and optional ranges. However, any lower limit can be combined with any upper limit to form an unambiguous range; and any lower limit can be combined with other lower limits to form an unambiguous range. Similarly, any upper limit can be combined with any other upper limit to form an unambiguous range; the optional items in the optional range can also be combined arbitrarily.

[0038] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art.

[0039] In the present invention, after silane is adsorbed and pyrolyzed on porous carbon, a layer of highly conductive, high-temperature, and oxidation-resistant MXene coating is coated on the material through liquid phase coating, and then a layer of carbon coating is performed. Under the protection of the MXene conductive, high-temperature, and oxidation-resistant coating, the temperature can be increased to fully graphitize the product; the highly conductive, high-temperature, and oxidation-resistant MXene coating is formed by modified MXene material, and its preparation is as follows: first, the etchant formula is improved to reduce the fluorine groups on the surface of MXene to enhance the thermal stability of the material, and then boron-containing graphene quantum dots are introduced to protect the positively charged end faces of MXene, and finally, protonated graphene quantum dots are introduced to construct a P / N heterostructure to further improve the conductivity and stability of the MXene slurry.

[0040] The MAX phase in the present application includes but is not limited to: one of Ti3AlC2, Ti2AlC, V2AlC, Nb2AlC, and V4AlC3 (relative molecular weight less than 300).

[0041] In some embodiments, the process of preparing MXene by etching the MAX phase with an etchant is as follows: etching Ti3AlC2(MAX) with lithium fluoride and hydrochloric acid at 35-60° C. for 24-48 h, adjusting the pH of the solution to neutral, and then centrifuging and washing to collect Ti3C2T X (MXene), and 10%-25% by mass of 1M ascorbic acid was added thereto.

[0042] Preferably, the etching temperature is 45°C and the etching time is 48h; deionized water is added and centrifuged at 3500rpm for 5min to wash away the residual etchant in the solution, and the pH of the solution is adjusted to 6; through multiple mixing-centrifugation-mixing steps, the upper liquid is a thick black liquid, which is Ti3C2T X (MXene); Ti3C2T X A 1M ascorbic acid solution with a mass ratio of 15% was added to the (MXene) solution to obtain a MXene solution concentration of 120 mg / mL.

[0043] In some embodiments, the process of preparing graphene quantum dots B-GQD is: dissolving citric acid and boric acid in deionized water, stirring evenly, and heating at 150-180° C. for 240-420 min to prepare B-GQD.

[0044] Preferably, the mass ratio of citric acid to boric acid is 20:1.3; the heating temperature is 180° C., and the heating time is 180 min.

[0045] In some embodiments, graphene quantum dots P-GQD are prepared + The process is as follows: dissolve citric acid and phytic acid in deionized water, stir evenly and heat at 150-180°C for 120-360 min, adjust the solution pH to 1-3 after dissolution, and obtain the product P-GQD + .

[0046] Preferably, the mass ratio of citric acid to phytic acid is 20:1.3, the heating temperature is 180° C., and the heating time is 180 min; the pH value of the solution is adjusted to 2 by hydrochloric acid solution.

[0047] In some embodiments, the process for preparing the modified MXene material B / P-GQD / MXene is as follows: adding B-GQD and P-GQD to MXene + The modified MXene slurry with high conductivity, high temperature resistance and oxidation resistance is obtained through self-assembly by electrostatic force.

[0048] Preferably, B-GQD and P-GQD + The addition amounts are 15wt% and 10wt% respectively, and the stirring time is 10-20min.

[0049] In some embodiments, the process for preparing the porous carbon material with deposited silicon nanoparticles is:

[0050] The acid-based resin: organic base pore-forming agent is mixed and reacted at room temperature for 12-24 hours in a mass ratio of 100:1-10, and then dried in a spray drying device at an inlet temperature of 240°C, an outlet temperature of 70°C, and a flow rate of 1kg / h. The obtained material is transferred to a tubular furnace and carbonized at a temperature of 700-900°C for 1-6 hours;

[0051] Silane gas is introduced into the pores of the porous carbon substrate using CVD technology (vapor deposition method), and the gas is precipitated into silicon nanoparticles dispersed in the pores of the porous carbon through high-temperature pyrolysis. The deposited silicon nanoparticles occupy 45%-55% of the porous carbon pores;

[0052] The porous carbon material with deposited silicon nanoparticles was coated by liquid phase method, and the material was soaked in a highly conductive, high temperature and oxidation resistant MXene slurry with a solid content of 100 mg / mL for 60-90 minutes. Then, a spray dryer was used under the conditions of an inlet temperature of 240°C, an outlet temperature of 70°C, and a flow rate of 1 kg / h to obtain a silicon-carbon material with a B / P-GQD / MXene coating;

[0053] Finally, acetylene gas is introduced to coat the product in step three with another layer of carbon, and the temperature is raised to 1000° C.-1200° C. and reacted for 4-6 hours to graphitize the carbon material.

[0054] Preferably, the mass ratio of acid-based resin: organic base pore-forming agent is 100:5; the mixing reaction time of acid-based resin and organic base pore-forming agent is 12 hours; the temperature of carbonization furnace is 700°C, and the carbonization time is 3 hours; the volume ratio of deposited silicon nanoparticles is 47%; the immersion time is 80 minutes; the graphitization temperature is 1200°C, and the graphitization time is 4 hours.

[0055] In the present application, the negative electrode active material layer includes, by mass percentage, 90%-97% of negative electrode active material (negative electrode main material and silicon-carbon composite material), 1%-2.5% of conductive agent, 1.2%-2.5% of binder and 0.5%-1.5% of dispersant.

[0056] In the present application, the conductive agent can be selected from at least one of carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanotubes, metal powder, and graphene; the binder can be selected from at least one of carboxymethyl cellulose, styrene-butadiene rubber, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate; the dispersant can be selected from at least one of sodium carboxymethyl cellulose, triethylhexyl phosphoric acid, and sodium dodecyl sulfate.

[0057] The present invention provides a battery, which comprises the negative electrode sheet mentioned above.

[0058] The present invention does not specifically limit the positive electrode sheet, separator, and electrolyte of the battery.

[0059] Illustratively, the positive electrode active material may be selected from commonly used positive electrode active materials in the art, such as one or more of lithium cobalt oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese phosphate, and lithium iron phosphate.

[0060] For example, any known porous structured diaphragm with electrochemical stability and chemical stability may be selected as the diaphragm.

[0061] Exemplarily, the organic solvent used to transport ions in the electrolyte can be ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), diethyl sulfone (ESE) at least one. In a specific embodiment, two or more of the above organic solvents can be selected.

[0062] Exemplarily, the ion source in the electrolyte salt can be selected from lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium hexafluoroantimonate (LiSbF6), lithium difluorophosphate (LiPF2O2), 4,5-dicyano-2-trifluoromethylimidazolium lithium (LiDTI), lithium bis(oxalate)borate (LiBOB), lithium trifluoromethanesulfonate (LiTFS), lithium bis(malonate)borate (LiBMB), lithium difluorooxalateborate (LiDFOB), lithium bis(difluoromalonate)borate (LiBDFMB) , lithium (malonate oxalate) borate (LiMOB), lithium (difluoromalonate oxalate) borate (LiDFMOB), lithium tri(oxalate) phosphate (LiTOP), lithium tri(difluoromalonate) phosphate (LiTDFMP), lithium tetrafluorooxalate phosphate (LiTFOP), lithium difluorobis(oxalate) phosphate (LiDFOP), lithium bis(fluorosulfonyl) imide (LiFSI), lithium bis(trifluoromethanesulfonyl) imide (LiTFSI), lithium (fluorosulfonyl)(trifluoromethanesulfonyl) imide (LiN(SO2F)(SO2CF3)), lithium nitrate (LiNO3), and lithium fluoride (LiF).

[0063] Exemplarily, the additive in the electrolyte can be vinylene carbonate (VC), vinyl ethylene carbonate (VEC), 1,3-propane sultone, fluoroethylene carbonate (FEC), trifluoromethyl vinyl carbonate, dimethyl sulfate, vinyl sulfate, methyl vinyl sulfate, propylene sulfate, vinyl sulfite, succinic anhydride, biphenyl, biphenyl ether, toluene, xylene, cyclohexylbenzene, fluorobenzene, p-fluorotoluene, p-fluoroanisole, tert-butylbenzene, tert-amylbenzene, propylene sultone, butane sultone, methylene disulfonate, ethylene glycol bis(propionitrile) ether, hexamethyldisilazane, heptamethyldisilazane, dimethyl methylphosphonate, diethyl ethylphosphonate, trimethyl phosphate, triethyl phosphate, triphenyl phosphate, triphenyl phosphite, At least one of tris(trimethylsilyl)borate, tris(trimethylsilyl)phosphate, acetonitrile (AN), malononitrile, succinonitrile (SN), glutaronitrile (GN), adiponitrile (ADN), 1,3,6-hexanetricarboxylic acid nitrile, 1,3,5-pentanetricarboxylic acid nitrile, ethylene glycol bis(propionitrile), hexafluorocyclotriphosphazene, pentafluoroethoxycyclotriphosphazene, pentafluorophenoxycyclotriphosphazene, 1,4-dicyano-2-butene, p-fluorobenzonitrile, p-methylbenzonitrile, 2-fluoroadiponitrile, 2,2-difluorosuccinonitrile, tricyanobenzene, acrylonitrile, crotononitrile, trans-butenediconitrile, trans-hexenediconitrile, 1,2-bis(cyanoethoxy)ethane, 1,2,3-tris(cyanoethoxy)propane, bis(cyanoethyl)sulfone and 3-(trimethylsilyloxy)propionitrile.

[0064] The present invention is further described in detail below in conjunction with specific embodiments:

[0065] Ti3C2T X Preparation of (MXene):

[0066] Ti3AlC2(MAX) was etched using a combination of LiF and HCl etchants. The specific steps are to add 120±1.2mL HCl (9M) and 10±0.1g LiF to a polytetrafluoroethylene beaker and stir for 30min. Then slowly add 10.5±0.1g Ti3AlC2 and etch at 45°C for 48h. After the reaction is completed, separate at 3500rpm for 5min until the liquid pH is 5 to 7. Then add 40mL ethanol to the centrifuge tube, centrifuge at 10000rpm for 10min, and collect the lower sediment. Add deionized water to the centrifuge tube with the precipitate, shake it by hand, centrifuge it at 3500rpm for 5min to collect the dark green upper liquid, and finally add a 15% 1M ascorbic acid solution to the MXene solution to obtain a MXene solution concentration of 120mg / mL.

[0067] Preparation of Boron-doped Graphene Quantum Dots (B-GQD):

[0068] B-GQDs were prepared by thermal decomposition of citric acid and boric acid. Citric acid and boric acid were mixed in a mass ratio of 20:1.3 and heated at 180°C for 6 h by hydrothermal method (graphene sheet size was in the range of 25-30 nm). The obtained B-GQD crude product was dissolved in ultrapure water to obtain 100 mg mL -1 The B-GQD solution was finally filtered and dialyzed to remove the large carbon sheets and unreacted raw materials, and the B-GQD solid product was obtained after freeze-drying.

[0069] Phosphorus-doped graphene quantum dots (P-GQD + ) Preparation:

[0070] Preparation of P-GQDs by pyrolysis of citric acid and phytic acid followed by protonation with HCl + . Citric acid and phytic acid were mixed in a mass ratio of 20:1.3 and heated at 180°C for 6h by a hydrothermal method (the size of the graphene sheet was in the range of 25-30nm). + The crude product was dissolved in ultrapure water to obtain 100 mg mL -1 P-GQD + Aqueous solution. Add 1 molL -1 HCl was used to adjust the overall pH of the solution to 2. Finally, the large carbon sheets and unreacted raw materials were removed by filtration and dialysis, and P-GQDs were obtained after freeze-drying. + Solid product.

[0071] Preparation of highly conductive, high temperature and oxidation resistant modified MXene slurry (B / P-GQD / MXene):

[0072] Addition of B-GQDs and P-GQDs to MXene + (The added amounts are 15wt% and 10wt%, respectively) and stirred thoroughly for 10 to 20 minutes to obtain a highly conductive, high temperature, and oxidation-resistant modified MXene slurry (B / P-GQD / MXene).

[0073] Preparation of silicon-carbon composite materials:

[0074] The acid-based resin and organic base pore-forming agent were mixed and reacted at a mass ratio of 100:5 at room temperature for 12 hours, and then dried in a spray drying device at an inlet temperature of 240°C, an outlet temperature of 70°C, and a flow rate of 1kg / h. The obtained material was transferred to a tube furnace and carbonized at a temperature of 800°C for 3 hours; silane gas was introduced into the pores of the porous carbon substrate by CVD method, and the gas was precipitated into silicon nanoparticles dispersed in the pores of the porous carbon by high-temperature pyrolysis, and the deposited silicon nanoparticles accounted for 47% of the porous carbon voids; the porous carbon material with deposited silicon nanoparticles was coated with a liquid phase coating method, and the material was soaked in a high-conductivity, high-temperature, and oxidation-resistant MXene slurry with a solid content of 100 mg / mL for 80 minutes. Then, a spray dryer was used at an inlet temperature of 240°C, an outlet temperature of 70°C, and a flow rate of 1kg / h to obtain a silicon-carbon material with a B / P-GQD / MXene coating. Finally, acetylene gas is introduced to coat the product in step three with another layer of carbon, and the temperature is raised to 200° C. and reacted for 4 hours to graphitize the carbon material.

[0075] Preparation of negative electrode sheet and battery:

[0076] Preparation of negative electrode sheet: Graphite: modified MXene protected silicon carbon material: acetylene black: carboxymethyl cellulose lithium (CMC): PAA: styrene butadiene rubber (SBR) are homogenized in a mass ratio of 89:8.5:0.5:0.5:1.5 and stirred thoroughly, and deionized water is added to adjust the solid content to 52.1% to obtain the required slurry. The above negative electrode slurry is coated on 6μ copper foil by a coater, and the double-sided coating amount is 13mg cm2. The negative electrode sheet is baked in an oven. The thickness of the negative electrode sheet after rolling is 85μm. A slitting machine is used to obtain a negative electrode sheet with a width of 40.3mm.

[0077] Preparation of batteries: Batteries containing silicon-carbon materials protected by modified MXene are prepared on fixed battery models. The negative electrode sheet preparation method is as above. The positive electrode sheet and separator specified in the model are selected, and an electrode group of qualified size is prepared by a winding machine. After packaging, liquid injection, standing, formation, capacity division, and sorting processes, a battery containing silicon-carbon materials protected by modified MXene is obtained.

[0078] Example 1

[0079] The specific test plan described above was adopted.

[0080] Embodiment 2-6

[0081] MAX (Ti2AlC, V2AlC, Nb2AlC, V4AlC3, Nb4AlC3) were selected respectively to prepare the corresponding modified MXene materials, and battery tests were carried out according to the above specific experimental plan.

[0082] The test results are shown in Table 1.

[0083] Table 1

[0084]

[0085] By comparing Examples 2-6 with Example 1, it can be seen that Ti3C2T X With the best conductive properties, it has outstanding low-temperature cycling and 0℃ cycling capabilities, a relatively small electrode expansion rate and the best 10C rate discharge performance.

[0086] Embodiment 7-16

[0087] Referring to the above specific implementation scheme, the difference is that different concentrations of Ti3C2T X (10, 20, 30, 40, 50, 60, 70, 80, 90, 100mg mL -1 ), the test results are shown in Table 2.

[0088] Table 2

[0089]

[0090] By comparing Examples 7-16, it can be seen that as the concentration of MXene increases, the battery 10C discharge energy retention rate and the pole piece expansion rate show a trend of first increasing and then slowly decreasing. This may be because as the concentration increases, the van der Waals force between the MXene interlayer nanosheets is further enhanced, causing the nanosheets to gradually accumulate and resulting in a decrease in conductivity. 120 mg mL -1 MXene is the best concentration choice.

[0091] Examples 17-21

[0092] Referring to the above specific implementation manner, the difference is that the amount of B-GQD participating in the electrostatic self-assembly is 5%, 10%, 20%, and 25%. The test results are shown in Table 3.

[0093] Table 3

[0094]

[0095]

[0096] Examples 21-24

[0097] Referring to the above specific implementation, the difference is that P-GQD + The amounts are 5%, 15%, 20%, and 25%. The test results are shown in Table 4.

[0098] Table 4

[0099]

[0100] By comparing Test Examples 21-24 with the comparative examples and Examples 17-20 with the comparative examples, it can be seen that with the incorporation of quantum dots, the cycle retention rate shows a trend of first increasing and then decreasing. This may be because quantum dots, as semiconductor materials, affect conductivity to a certain extent as their dosage increases.

[0101] Examples 25-32

[0102] Referring to the above specific embodiments, the difference is the liquid phase coating immersion time (10min, 20min, 30min, 40min, 50min, 60min, 80min, 100min, 120min) during the synthesis of the silicon-carbon composite material. The test results are shown in Table 5.

[0103] Table 5

[0104]

[0105]

[0106] As the liquid phase coating time increases, the performance data generally rise first and then tend to be flat. Considering the comprehensive process time, the liquid phase coating time is selected as 80 minutes.

[0107] Comparative Example 1

[0108] A silicon-carbon composite material without a protective layer was used, and the rest was referred to the above specific embodiment. The test results are shown in Table 6.

[0109] Comparative Example 2

[0110] Graphene was used as the protective layer of the silicon-carbon composite, and the rest was referred to the above specific embodiment. The test results are shown in Table 6.

[0111] Comparative Example 3

[0112] Carbon nanotubes were used as the protective layer of the silicon-carbon composite, and the rest was referred to the above specific embodiment. The test results are shown in Table 6.

[0113] Table 6

[0114]

[0115] By comparing Example 1 with Comparative Examples 1-3, it can be found that the use of the highly conductive, high temperature and oxidation resistant modified MXene material of the present application as a protective layer has a better overall effect, while effectively protecting silicon nanoparticles, enhancing the conductivity of the silicon-carbon composite.

[0116] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, according to the technical essence of the present invention, any simple modification, equivalent replacement and improvement made to the above embodiment still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a silicon-carbon composite material based on modified MXene, characterized in that: The following steps are involved: Prepare MXene by etching the MAX phase with an etchant; Prepare graphene quantum dots B-GQD and P-GQD respectively + ; The graphene quantum dots B-GQD and P-GQD + Self-assembly with the MXene through electrostatic adsorption to form a modified MXene material B / P-GQD / MXene; Preparation of porous carbon materials depositing silicon nanoparticles; The modified MXene material B / P-GQD / MXene is used to perform liquid phase coating on a porous carbon material with deposited silicon nanoparticles to form a silicon-carbon composite material based on the modified MXene.

2. The method for preparing a silicon-carbon composite material based on modified MXene according to claim 1, characterized in that: The etchant is lithium fluoride and hydrochloric acid; the MAX is Ti3C2T X .

3. The method for preparing a silicon-carbon composite material based on modified MXene according to claim 1, characterized in that: Addition of B-GQDs and P-GQDs to MXene + The addition amounts were 15wt% and 10wt%, respectively.

4. The method for preparing a silicon-carbon composite material based on modified MXene according to claim 1, characterized in that: The etching time is 12h-48h, and the etching temperature is 25°C-40°C; after etching, the pH of the solution is adjusted to neutral to collect MXene, and ascorbic acid is added to the MXene obtained by etching.

5. The method for preparing a silicon-carbon composite material based on modified MXene according to claim 1, characterized in that: The graphene quantum dots B-GQD are prepared by hydrothermal method using citric acid and boric acid, and the graphene quantum dots P-GQD + It is prepared from citric acid and phytic acid by a hydrothermal method.

6. The method for preparing a silicon-carbon composite material based on modified MXene according to claim 1, characterized in that: The method for preparing the porous carbon material with deposited silicon nanoparticles is as follows: The acid-based resin and the organic base pore-forming agent are mixed and reacted in a mass ratio of 100:1-10, and after drying, carbonized at a temperature of 700-900°C for 1-6h; Silane gas is introduced into the pores of the porous carbon substrate by vapor deposition, and the gas is precipitated into silicon nanoparticles dispersed in the porous carbon pores through high-temperature pyrolysis, so that the deposited silicon nanoparticles occupy 45%-55% of the porous carbon void volume.

7. The method for preparing a silicon-carbon composite material based on modified MXene according to claim 1, characterized in that: The liquid phase coating time is 60 minutes to 100 minutes, and the modified MXene-based silicon-carbon composite material is obtained by drying after the liquid phase coating.

8. The silicon-carbon composite material based on modified MXene prepared by the method according to any one of claims 1 to 7, characterized in that: The surface of the silicon-carbon composite material has a modified MXene protective layer, and the modified MXene protective layer contains a P / N heterogeneous structure.

9. A negative electrode sheet, characterized in that: The negative electrode sheet comprises the silicon-carbon composite material according to claim 8.

10. A battery, characterized in that: The battery comprises the negative electrode sheet according to claim 9.

Citation Information

Cited By

  • Phosphonic acid modified high-entropy MXene composite diaphragm and preparation method thereof

    CN120933595A

  • Composite conductive paste and preparation method thereof, negative electrode material, negative electrode plate and battery

    CN121583929A